Implementasi Sistem Active Directory Untuk Kemudahan Administrasi Laboratorium – Laboratorium Program Studi Teknik Informatika Universitas Kristen Petra - Vincentius Aditya Nugraha; Agustinus Noertjahyana; Ibnu Gunawan (Jurnal Infra, 2014)
The presence of computer laboratory is really helpful in terms of supporting the learning process in the college scope. But the user of the computer itself tend to irresponsibly making change(s) the computer’s configuration. The configuration made by the laboratory’s assistant itself can sometimes be wrong, making the fix to the configuration itself has to be made on each of the computer.The use of Active Directory can be spread easily via server. The limitations of a user group applied based on its own functions. The users itself get their personal space for storing their data in the server, in which if one user uses another computer in the lab, he / she still can access his / her data. Administration also centered on the server thatfacilitate lab’s assistants on helping their task. The re-installation of the computer’s operating system is made easy by using the remote install hosted by server.The result from the usage of Active Directory system is that it will help the administration tasks done by the lab’s assistants, especially on the limitations that should be applied to the groups of users. Personal storage space in the server also helps the students on the availability of their data, regardless where or which computer they are using.